A classical S2 spin system with discrete out-of-plane anisotropy: Variational analysis at surface and vortex scalings. (June 2023) - Cicalese, Marco; Orlando, Gianluca; Ruf, Matthias
Abstract: We consider a classical Heisenberg system of S 2 spins on a square lattice of spacing ɛ . We introduce a magnetic anisotropy by constraining the out-of-plane component of each spin to take only finitely many values. Computing the Γ -limit of a suitable scaling of the energy functional as ɛ → 0 we prove that, in the continuum description, the system concentrates energy at the boundary of sets in which the out-of-plane component of the spin is constant. In a second step we analyze a different scaling of the energy and we prove that, in each of such phases, the energy can further concentrate on finitely many points corresponding to vortex-like singularities of the in-plane components of the spins.